Illicit financial flows and country-by-country reporting in extractive industries - Saila Stausholm; Petr Janský; Marek Šedivý (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Economic data are important in governing the international political economy. Some of the most widely used macro statistics risk being undermined by systematic misalignment in reporting of economic activity due to illicit financial flows, as well as tax-minimizing financial transactions by multinational corporations. Measuring these misalignments may prove a way to correct old statistical standards, if adequate data can be obtained. We evaluate whether new transparency and reporting regimes that require country-by-country reporting by multinational corporations could prove a feasible way to appropriate the amount of tax avoidance and use these figures to correct macro statistics. We evaluate the existing data for two of the standards through previous literature and provide original analysis of a third standard that is applied to the extractive industries. We find that the standards lack coherence and workability, and that particularly the extractive industry standard falls short of enabling thorough research on profit reporting and taxmotivated misalignments by multinational corporations.
Keywords: C82; E01; H25; G28; 330; economic data; tax avoidance; illicit financial flows; country-by-country reporting; extractive industries